(untitled) (Experimental biology, 2015)
The interaction 749 miRNA of Bos taurus genome with 20 MYB transcription factors family genes mRNA was studied. Installed 58 miRNA binding sites with eight MYB family gene mRNA. In mRNA each of the genes identified from three binding sites for gene MYBL1 to 21 binding sites for gene NCOR1. MiR-1260b had binding sites in mRNA MIER1, NCOR1, RCOR1 genes. Nine miRNA had binding sites in mRNA of two genes. The of ΔG / ΔGm value, characterizing the degree of affinity miRNA to mRNA, varied from 85 to 90%. The role of bta-miRNA in the regulation expression of MYB transcription factors target genes are discussed.